THE METHODOLOGY FOR INSTRUCTING ORAL TEXT COMPOSITION IN PRIMARY EDUCATION WITHIN THE FRAMEWORK OF MOTHER TONGUE AND READING LITERACY COURSES. - Baxronova Sarvinoz Akbar qizi; Haydarova Mahliyo Amrillo qizi (KONFERENSIYALAR, 2025)
Аnnotation. This article explores the significance of teaching methodologies for oral text composition in primary school mother tongue and literacy classes, and their role in enhancing students’ language acquisition and logical thinking skills. It examines the main methods used in teaching oral text construction, their impact on learners, as well as innovative approaches informed by international experience. The article also provides practical recommendations relevant to the education system in Uzbekistan.